2016
DOI: 10.2147/copd.s113510
|View full text |Cite
|
Sign up to set email alerts
|

Community-acquired pneumonia and survival of critically ill acute exacerbation of COPD patients in respiratory intensive care units

Abstract: PurposeThe aim of this study was to appraise the effect of community-acquired pneumonia (CAP) on inhospital mortality in critically ill acute exacerbation of COPD (AECOPD) patients admitted to a respiratory intensive care unit.Patients and methodsA retrospective observational study was performed. Consecutive critically ill AECOPD patients receiving treatment in a respiratory intensive care unit were reviewed from September 1, 2012, to August 31, 2015. Categorical variables were analyzed using chi-square tests,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 27 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…10 The patients with pneumonic exacerbation have been found to be admitted to intensive care units more often and stay there longer than those with non-pneumonic exacerbations. 11 The use of corticosteroids has a beneficial effect on severe AECOPD patients and also increases the risk of pneumonia. 11,12 In-hospital mortality in COPD complicated by community-acquired pneumonia has been reported to be 12.2%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 The patients with pneumonic exacerbation have been found to be admitted to intensive care units more often and stay there longer than those with non-pneumonic exacerbations. 11 The use of corticosteroids has a beneficial effect on severe AECOPD patients and also increases the risk of pneumonia. 11,12 In-hospital mortality in COPD complicated by community-acquired pneumonia has been reported to be 12.2%.…”
Section: Introductionmentioning
confidence: 99%
“…11 The use of corticosteroids has a beneficial effect on severe AECOPD patients and also increases the risk of pneumonia. 11,12 In-hospital mortality in COPD complicated by community-acquired pneumonia has been reported to be 12.2%. 13…”
Section: Introductionmentioning
confidence: 99%
“…Infectious exacerbations or end-stage disease have been identified as major causes of ICU admittance [12][13][14] . As yet, many studies have attempted to identify independent predictors of the outcomes of these patients in the ICU, however, the results are not consistent across studies, except for Acute Physiology and Chronic Health Evaluation (APACHE)-II score which seems to have a reproducible effect [15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has demonstrated that serum PCT levels are elevated following bacterial infection, and PCT has been proven to be a useful marker for early diagnosis of bacterial infection and for measuring infectious severity 11, 12, 13, 14. CRP is an acute-phase protein that becomes elevated during infections such as pneumonia and sepsis, and it is predominantly produced by liver cells 15, 16. However, from the viewpoint of the authors, limited information is available on the significance of PCT and CRP in the diagnosis of infection in GPP patients.…”
Section: Introductionmentioning
confidence: 99%